Dams: Impacts and Hazards - Silva, Ana Maria (2022)
In the first year of operation of the biggest artificial lake of Europe, Alqueva, which is still in a refilling period, this meeting aims to evaluate the negative and positive impacts of this kind of impoundment. Invited scientists and experts, who belong to a wide variety of scientific areas, with a broad range of viewpoints about this subject, will give an embraced overview about impacts and hazards of dams and its reservoirs.